2007
DOI: 10.1111/j.1749-7345.2006.00073.x
|View full text |Cite
|
Sign up to set email alerts
|

Fly Prepupae as a Feedstuff for Rainbow Trout, Oncorhynchus mykiss

Abstract: Fly larvae may provide an effective method to mitigate two large and growing global concerns: the use of fish meal derived from capture fisheries in aquaculture diets and manure management in livestock and poultry facilities. A 9‐wk feed trial was conducted to determine whether fly larvae could be used as a partial fish meal and fish oil replacement in rainbow trout, Oncorhynchus mykiss, diets. A trout diet was formulated to contain 40% crude protein and 15% fat. Sixty‐seven percent of the protein in the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
257
6
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 389 publications
(288 citation statements)
references
References 18 publications
19
257
6
6
Order By: Relevance
“…Other livestock and fish species that have shown positive results by feeding them meal of different insect species such as Black soldier fly, Domesticated house fly, the Oriental latrine fly Chrysomya megacephala (Diptera: Calliphoridae), Yellow mealworm, the Domesticated silkworm Bombyx mori (Lepidoptera: Bombycidae) and the Variegated grasshopper Zonocerus variegatus (Orthoptera: Pyrgomorphidae) are: broiler chickens (56,57) ; tilapia (55,58,59) , African giant snail (Achatina spp.) (60) , African catfish Clarias gariepinus (61)(62)(63)(64)(65)(66)(67) ; and Rainbow trout Oncorhynchus mykiss (68,69) .…”
Section: Insects As Feedmentioning
confidence: 99%
“…Other livestock and fish species that have shown positive results by feeding them meal of different insect species such as Black soldier fly, Domesticated house fly, the Oriental latrine fly Chrysomya megacephala (Diptera: Calliphoridae), Yellow mealworm, the Domesticated silkworm Bombyx mori (Lepidoptera: Bombycidae) and the Variegated grasshopper Zonocerus variegatus (Orthoptera: Pyrgomorphidae) are: broiler chickens (56,57) ; tilapia (55,58,59) , African giant snail (Achatina spp.) (60) , African catfish Clarias gariepinus (61)(62)(63)(64)(65)(66)(67) ; and Rainbow trout Oncorhynchus mykiss (68,69) .…”
Section: Insects As Feedmentioning
confidence: 99%
“…Proximate analysis of BSF larvae contained 41.1-43.6% crude protein (CP), 15.0-34.8% ether extract (EE), 7.0% crude fibre (CF), 14.6-28.4% ash and 5278.49 kcal/kg gross energy (GE) on DM basis (Arango Gutierrez et al 2004;St-Hilaire et al 2007). Arango Gutierrez et al (2004) reported that larvae are rich in calcium (Ca; 5-8% DM) and phosphorus (P; 0.6-1.5% DM), however, other minerals profile is potassium (K; 0.69% DM), sodium (Na; 0.13% DM), magnesium (Mg; 0.39% DM), iron (Fe; 0.14% DM), manganese (Mn; 246 mg/kg DM), zinc (Zn; 108 mg/kg DM) and copper (Cu; 6.0 mg/kg DM).…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Total lipid content also increased from 21% to 30% DM. Feeding BSF larvae reared on cow manure and 22% of fish offal within 24 h of their pupation was sufficient for a substantial enrichment in polyunsaturated fatty acid (PUFA), especially in docosahexaenoic acid and eicosapentaenoic acid (St-Hilaire et al 2007). Recently, Maurer et al (2016) reported that dried full-fat BSF larvae meal contained 41.5% CP, 26.5% EE, 4.3% ash, 0.80% Ca, 0.50% P, 0.08% Na and 0.33% chloride while dried partly-defatted BSF larvae meal consisted 59.0% CP, 11.0% EE, 5.0% ash, 0.98% Ca, 0.63% P, 0.08% Na and 0.28% chloride .…”
Section: Chemical Compositionmentioning
confidence: 99%
“…They have a high dry matter (DM) content (35% to 45%), they are rich in lysine (6% to 8% of the CP), Ca (5% to 8% DM) and P (0.6% to 1.5% DM) (Makkar et al, 2014). Black soldier fly larvae are also rich in fat which has an extreme quantitative (15% to 49%) and qualitative variability depending on the chemical composition of the rearing substrate (St-Hilaire et al, 2007).…”
Section: Introductionmentioning
confidence: 99%